Manajemen Balance Scorecard dalam Meningkatkan Mutu Pendidikan di KB Muslimat Nu Nur Ikhlas Desa Bojongsana Kecamatan Suradadi Kabupaten Tegal - Muksin . (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
Balance scorecard management can assist the education process which includes a management system for continuous quality improvement and with balanced management in each unit. In its application in the world of education, it has four perspectives, financial, customer, process, and learning / growth perspectives. So it is necessary to study and conduct research on the management of school balance scorecards in improving the quality of education, especially in study groups (KB). This study aims to describe and explain (explanatory) BSC management carried out by KB Muslimat NU Nur Ikhlas, including describing the supporting resources used to improve the quality of education. This research is a qualitative research. Data collection used interviews, observation, and documentation, and the validity of the data used triangulation, and data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. The research results show that in terms of the quality of education achieved by KB Muslimat NU Nur Ikhlas it is relatively better for the PAUD level which has not been established for a long time. (1) The perspective of the Balanced Scorecard which is applied to non-profit organizations/institutions such as in the KB Muslimat NU Nur Ikhlas requires modification. If for profit organizations for a financial perspective are incoming cash and working capital, then for non-profit organizations the main focus is not on financial achievement, but on achieving customer-focused goals, in the context of government organizations is the community, then public services must be provided at a cost level competitive and efficient. (2) In the business world, whatever the business is, including business in educational services, namely Learning Groups (KB), in order to be successful in their business, they must provide satisfaction to their customers, both internal and external customers. (3) The ability to educate and train teachers is different, so an effort is needed to assist teachers in finding appropriate strategies and methods in learning so that they can guarantee quality improvement and solve their respective learning problems. (4) From the perspective of learning and growth with the aim of strategies to develop teacher creativity to develop quality and affordable learning methods, it can be measured by increasing teacher creativity and the variety of methods used in learning (outcome), as well as seen from the student: teacher ratio and the ratio of teaching aids : pupil.(quality control).